Peronospora pisi spore load on different leaves and its effect on chlorophyll, nucleic acid, protein and phenol contents of pea leaves - and R.S. DUBEY*, U.P. SINGH, B. PRITHIVIRAJ (Indian Phytopathology, 2002)
Peronospora pisi spore load on different nodal leaves and its effect on chlorophyll, protein, phenols and nucleic acid contents of pea leaves (cv. HUP 1) were studied. The maximum spore load (46 X 104 ) was observed on 18th nodal leaves at 23.51 per cent disease intensity. The chlorophyll, protein, phenols and nucleic acid content varied in the infected zone, healthy tissues near infection (0.5 cm away) and healthy leaves. Significant decrease in nucleic acids (RNA and DNA), phenols and chlorophyll was observed in the infected zone while total protein increased.